Stress and academic achievement among undergraduate students in Universiti Putra Malaysia - Elias, Habibah; Wong, Siew Ping; Abdullah, Maria Chong (Elsevier, 2011)
The objective of this study was to investigate the stress and academic achievement of undergraduate students in a local university from different disciplinary areas. Through cluster sampling, a total of 376 undergraduate students were selected to participate in this research. Academic achievement of the undergraduate students referred to their results, Grade Point Average (CPA), for the previous semester. The College Undergraduate Stress Scale (CUSS) was used to evaluate students’ stress level. The stress levels of undergraduate students were compared based on their year of study in university, and their degree programs. The findings of the study showed that overall, the undergraduate students experienced moderate levels of stress. The medical students had the highest stress level among the students. Moreover, findings showed that the first-year students had low stress level. Most sources of stress were from students’ academic. It was also found that there is a significant but weak negative relationship between undergraduate students’ stress level and their academic achievement.